2022
DOI: 10.1002/jpen.2431
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition as a risk for mortality and functionality in critically ill older adults

Abstract: Background There is no specific recommendation for nutrition therapy for critically ill older adults. However, targeting energy and protein balance and avoiding fasting could improve outcomes in this population with high‐risk nutrition outcomes. This study aimed to evaluate the associations between nutrition and mortality/functionality in critically ill older patients. Methods A single‐center retrospective observational study of critically ill patients aged 65 years or older was conducted. We extracted data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…The study by Agarwal et al evaluated 3,122 patients with a mean age of 64.6 ± 18 years and concluded that participants suffering from malnutrition were 41% ( 4 ). In critically ill elderly patients, malnutrition was higher with poor outcomes, increased rates of infections, length of hospital stay, and mortality risks ( 5 ). More data are required to evaluate nutrition in critically ill elderly patients.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Agarwal et al evaluated 3,122 patients with a mean age of 64.6 ± 18 years and concluded that participants suffering from malnutrition were 41% ( 4 ). In critically ill elderly patients, malnutrition was higher with poor outcomes, increased rates of infections, length of hospital stay, and mortality risks ( 5 ). More data are required to evaluate nutrition in critically ill elderly patients.…”
Section: Introductionmentioning
confidence: 99%